For every positive integer , a sequence satisfies:
Given that and , find the value of .
This problem is a part of <Inconsequences!> series .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
From the original condition, we see that
( a n + 2 − a n + 1 ) n 2 + 2 ( a n + 2 − a n + 1 ) n + ( − a n + 1 + a n ) n + ( − a n + 1 + a n ) = 0 ( n 2 + 2 n ) ( a n + 2 − a n + 1 ) = ( n + 1 ) ( a n + 1 − a n )
Note that a 2 = a 1 .
If a n + 1 = a n ,
( n 2 + 2 n ) ( a n + 2 − a n + 1 ) = ( n + 1 ) ( a n + 1 − a n ) = 0 .
∴ a n + 2 = a n + 1 .
Therefore, using above induction, we conclude that for every positive integer n , a n + 1 = a n .
Then we can transform the equation.
a n + 1 − a n a n + 2 − a n + 1 k = 1 ∏ n − 1 a k + 1 − a k a k + 2 − a k + 1 = n ( n + 2 ) n + 1 = k = 1 ∏ n − 1 k ( k + 2 ) k + 1
Note that n must be larger than or equal to 2 .
a 2 − a 1 a n + 1 − a n a n + 1 − a n = ( n − 1 ) ! ⋅ 2 ( n + 1 ) ! n ! ( n ≥ 2 ) = 1 4 4 ⋅ ( n + 1 ) ! n ( n ≥ 2 )
Now let's get some sum.
k = 2 ∑ n − 1 ( a k + 1 − a k ) a n − a 2 a n = 1 4 4 k = 2 ∑ n − 1 ( k + 1 ) ! k ( n ≥ 3 ) = 1 4 4 k = 2 ∑ n − 1 ( k ! 1 − ( k + 1 ) ! 1 ) ( n ≥ 3 ) = 1 2 1 + 1 4 4 ( 2 1 − n ! 1 ) ( n ≥ 3 )
So we've got a n .
Then let's punch that into the limit we're trying to get a value of.
n → ∞ lim a n = n → ∞ lim ( 1 2 1 + 1 4 4 ( 2 1 − n ! 1 ) ) = 1 2 1 + 7 2 = 1 9 3
The answer is already found, but I'd like to elaborate more.
Substitute n = 1 , 2 to a n = 1 2 1 + 1 4 4 ( 2 1 − n ! 1 ) .
And we see that the equation holds.
Therefore, for every positive integer n ,
a n = 1 2 1 + 1 4 4 ( 2 1 − n ! 1 )